DOP Stimulates Heterotrophic Bacterial Production in the Oligotrophic Southeastern Mediterranean Coastal Waters - Sisma-Ventura, Guy; Rahav, Eyal (Frontiers in Microbiology, 2019)
Phytoplankton and heterotrophic bacteria rely on a suite of inorganic and organic macronutrients to satisfy their cellular needs. Here, we explored the effect of dissolved inorganic phosphate (PO4) and several dissolved organic molecules containing phosphorus (ATP, Glucose-6-Phosphate, 2-aminoethylphosphonic acid, collectively referred to as DOP), on the activity and biomass of autotrophic and heterotrophic microbial populations that can be found during summer in the coastal water of the Southeastern Mediterranean Sea (SEMS). To this end, surface waters were supplemented with PO4, one of the different organic molecules, or PO4+ATP, and measured the PO4 turnover time (Tt), alkaline phosphatase activity (APA), heterotrophic bacterial production (BP), primary production (PP), and the abundance of the different microbial components. Our results show that PO4 alone does not stimulate any significant change in most of the autotrophic/heterotrophic bacterial variables tested. ATP addition (alone or with PO4) triggers the strongest increase in primary and bacterial productivity/biomass. Heterotrophic bacterial abundance and BP respond faster than phytoplankton (24 h post addition) to the various additions of DOP or PO4+ATP, followed by a recovery of primary productivity (48 h post addition). These observations suggest that both autotrophic and heterotrophic microbial communities compete for labile organic molecules containing P, such as ATP, to satisfy their cellular needs. It also suggests that SEMS coastal water heterotrophic bacteria are likely C and P co-limited.